Lessons Learned from Influenza A(H1N1)pdm09 Pandemic Response in Thailand - Ungchusak, Kumnuan (Centers for Disease Control and Prevention, 2012)
In 2009, Thailand experienced rapid spread of the pandemic influenza A(H1N1)pdm09 virus. The national response came under intense public scrutiny as the number of confirmed cases and associated deaths increased. Thus, during July–December 2009, the Ministry of Public Health and the World Health Organization jointly reviewed the response efforts. The review found that the actions taken were largely appropriate and proportionate to need. However, areas needing improvement were surveillance, laboratory capacity, hospital infection control and surge capacity, coordination and monitoring of guidelines for clinical management and nonpharmaceutical interventions, risk communications, and addressing vulnerabilities of non-Thai displaced and migrant populations. The experience in Thailand may be applicable to other countries and settings, and the lessons learned may help strengthen responses to other pandemics or comparable prolonged public health emergencies.